PERUBAHAN POLA KOMUNIKASI MASYARAKAT DI ERA DIGITAL - Rohila; Sandika; M. Mujiburahman Hakim; Neidzar Ega Pratama; Sri Hertimi (Hujjah: Jurnal Ilmiah Komunikasi dan Penyiaran Islam, 2026)
The rapid development of digital technology and the increasingly massive penetration of the internet in the 21st century have brought fundamental transformations to societal communication patterns. This study aims to analyze changes in community communication patterns in the digital era, examining the shift from conventional communication to digital platform-based communication, as well as identifying the resulting social impacts. This research employs a qualitative descriptive-analytical approach through a systematic library research method, drawing on national and international scientific journals, communication theory textbooks, and official reports from relevant government institutions. Data analysis was conducted using an interactive analysis model encompassing three stages: data reduction, data presentation, and conclusion drawing. The findings indicate that digital technology has transformed the mass communication paradigm from a one-to-many model to a many-to-many communication model, marked by the emergence of social media platforms as the dominant means of interaction. This transformation has given rise to new communication dynamics: increased asynchronous communication, the substitution of nonverbal expressions by digital visual symbols, the formation of virtual communities transcending geographical boundaries, and the reconstruction of communication norms and digital etiquette. In addition to expanding the reach of social interaction and accelerating information flow, this change has also generated negative impacts, including the dehumanization of social relations, the proliferation of disinformation, and a widening digital divide within society.This study affirms that digital transformation is inevitable and continuously evolving, making the comprehensive strengthening of digital literacy across all segments of society an urgent necessity.